Postoperative Prescription of Low-dose Narcotics Yields Equivalent Pain Outcomes Compared to High-dose Narcotics in Opioid-naïve Patients Undergoing Spine Surgery. Issue 24 (15th December 2021) - Mohanty, Sarthak; Shin, Max; Casper, David; Saifi, Comron
Abstract : After adjusting for the heterogeneous spinal procedures, comorbidities, and perioperative pain, patients prescribed opioids <40 MME/day (equivalent to 5 tablets of 5 mg oxycodone/day) showed no difference in POD 30 pain (β: 0.095, P = 0.752) when compared to patients who received the highest dose analgesics (>80MME/day or 11 tablets of 5 mg oxycodone/day). Abstract : Study Design: Retrospective cohort study at a single institution. Patients undergoing specific, elective spinal procedures between 2012 and 2018. Objective: The aim of thi stsudy was to investigate the relationship between opioid prescriptions during the immediate, post-discharge period, and patient-reported pain outcomes. Summary of Background Data: Medically prescribed opiates contribute to the opioid crisis, manifesting in significant mortality and economic burden. Although opioids are a mainstay of pain amelioration following spinal surgery, prescription practices are heterogeneous. Methods: Inclusion criteria included: patients who underwent one of 10 spinal procedures (Table 1 ); patients with preoperative, postoperative day (POD 1, and POD 30 pain scores reported on the visual analog scale (VAS); patients discharged without a complicated perioperative course. Opioids were converted to morphine milligram equivalents per day (MME/day) using a standard reference table. χ 2, Kruskal-Wallis, and logistic regression were utilized to investigate associations between clinical variables and postoperative pain scores. Univariate and multivariable linear regression models with Stepwise selection (cut off: P = 0.05) were employed as appropriate on POD 30 VAS pain scores. Results: Smoking status and postoperative LOS were associated with opioid prescription doses. Patients prescribed opioids <40 MME/day, equivalent to five tablets of 5 mg oxycodone/day, showed no significant difference in POD 30 VAS score (β coefficient: 0.095, P = 0.752) when compared to patients who received the highest-dose opioids (>80 MME/day—equivalent to 10 tablets of 5 mg oxycodone/day). Adjusted multivariable logistic regression analysis revealed that postoperative opioid dosage/prescription was not a significant predictor of patients reporting at least 50% pain improvement, suggesting that 40 MME/day is sufficient to maintain patient satisfaction. Conclusion: Patients receiving the lowest dosage of opioid prescriptions with sufficient nonopiate analgesics did not report worse pain relief at POD 30 compared to those receiving higher opioid prescriptions. In light of the opioid epidemic, this study supports initial dosing recommendations by the American Society for Addiction Medicine. Level of Evidence: 3